The health landscape of central Kerala: insight into adult physical activity, obesity and awareness among rural adults - Aiyankovil, John G.; Baisil, Sharon; Daniel, Paul (International Journal Of Community Medicine And Public Health, 2023)
Background: Body mass index is a widely used index for assessing weight in relation to height, categorizing individuals as underweight, overweight, or obese. Obesity is a pervasive form of malnutrition globally, and Kerala ranks second in India for the highest prevalence of obese individuals, following Punjab. This reflects a growing preference for unhealthy lifestyles, contributing to rising comorbidities and overall ill-health. This study aims to assess the prevalence and relationship between overall physical activity and Body Mass Index among adults in a rural population. It also investigates the attitudes and awareness of the participants regarding obesity and physical activity. Methods: A sample of 204 individuals aged 18 to 64, from 125 households in the rural area of Kunnackal, participated in this study. Data were collected using a semi-structured questionnaire. Results: Out of 204 participants, 196 (96.07%) reported adequate physical activity, with 124 of them having a normal BMI. A higher prevalence of obesity was observed in the low physical activity group. Most participants demonstrated an understanding of the causes of obesity and the role of physical activity in maintaining a healthy life. Conclusions: Our study found that 96.07% of participants had adequate physical activity, and the majority (124) had a normal BMI. No significant association was observed between BMI and age, gender, or occupation. Most participants showed awareness of the causes of obesity and the importance of physical activity in promoting health.